2021
DOI: 10.31083/j.jin2004097
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of depiction of the intracranial arteries on brain CT angiography using deep learning reconstruction

Abstract: To evaluate the ability of a commercialized deep learning reconstruction technique to depict intracranial vessels on the brain computed tomography angiography and compare the image quality with filtered-back-projection and hybrid iterative reconstruction in terms of objective and subjective measures. Forty-three patients underwent brain computed tomography angiography, and images were reconstructed using three algorithms: filtered-back-projection, hybrid iterative reconstruction, and deep learning reconstructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The clear vessel delineation may sometimes be challenging owing to artifact and image noise in the posterior fossa and hinder the interpretation of the aneurysm or dissection in the vertebrobasilar system [ 25 ]. With the recent deep learning reconstruction, the image quality was significantly increased with a lower image noise and higher CNR, SNR, and spatial resolution, and the lesion detectability was also demonstrated to be better than the traditional filtered-back projection and iterative reconstruction methods [ 7 , 26 , 27 ]. The vertebrobasilar arteries were rated by both observers as having an excellent image quality in the CE-boost images than in conventional images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clear vessel delineation may sometimes be challenging owing to artifact and image noise in the posterior fossa and hinder the interpretation of the aneurysm or dissection in the vertebrobasilar system [ 25 ]. With the recent deep learning reconstruction, the image quality was significantly increased with a lower image noise and higher CNR, SNR, and spatial resolution, and the lesion detectability was also demonstrated to be better than the traditional filtered-back projection and iterative reconstruction methods [ 7 , 26 , 27 ]. The vertebrobasilar arteries were rated by both observers as having an excellent image quality in the CE-boost images than in conventional images.…”
Section: Discussionmentioning
confidence: 99%
“…To clearly visualize small intracranial vessels, various methods (deep learning reconstruction, ultra-high-resolution CT, etc.) have been introduced to accurately visualize small cerebral vessels on CT angiography [ 7 , 8 ]. Deep learning image reconstruction increases both quantitative and qualitative image analysis on CT angiography compared with other image reconstructions by training images through deep convolutional neural networks [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been reported that DLR provides lower image noise at lower tube voltage (30). In addition, the blooming artifact reduction is significantly improved with DLR compared with FBP and hybrid IR (21). These advantages could be applied to DLR with a lower radiation dose scanning protocol.…”
Section: Discussionmentioning
confidence: 99%
“…DLR was developed to reduce the image noise and improve spatial resolution through deep neural networks and its high-quality model-based iterative reconstruction (MBIR) or filtered back projection (FBP) training images, referred to as advanced intelligent clear-IQ engine (AiCE) (14) and TrueFidelity (15), respectively. Several clinical studies have demonstrated that the lesion detection rate and image quality of DLR are higher than those of iterative reconstruction (IR) for low-dose chest CT, abdominal CT, brain CTA, and coronary CTA (16)(17)(18)(19)(20)(21); however, there has been no evidence proving the effect of different contrast media iodine concentrations on DLR in coronary CTA. Enhancing vascular attenuation through DLR decreases the iodine load in patients with renal impairment.…”
Section: Introductionmentioning
confidence: 99%
“…TrueFidelity™ is trained with high-quality FBP images while AiCE is developed using high-quality advanced model-based IR images. Both latter methods have reported accurate identification, detection, and classification of abnormal lesions in clinical settings (17,(19)(20)(21)(22). The CAC quantification with DLR (AiCE) has not been investigated to our knowledge.…”
Section: Introductionmentioning
confidence: 99%